2008
DOI: 10.1111/j.1468-0009.2008.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Message Design Strategies to Raise Public Awareness of Social Determinants of Health and Population Health Disparities

Abstract: Context:Raising public awareness of the importance of social determinants of health (SDH) and health disparities presents formidable communication challenges.Methods: This article reviews three message strategies that could be used to raise awareness of SDH and health disparities: message framing, narratives, and visual imagery. Findings:Although few studies have directly tested message strategies for raising awareness of SDH and health disparities, the accumulated evidence from other domains suggests that pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
162
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(177 citation statements)
references
References 77 publications
7
162
1
1
Order By: Relevance
“…Starting from the family, educational institutions, social institutions, employers, industrialists, the government and society, 33 each factor of them can build political management skills through complementary work and research findings [93]. In addition, it is a fruitful work to recruit the media as a social policy to highlight the factors affecting the health and health promotion [94].…”
Section: Discussion and Recommendationmentioning
confidence: 99%
“…Starting from the family, educational institutions, social institutions, employers, industrialists, the government and society, 33 each factor of them can build political management skills through complementary work and research findings [93]. In addition, it is a fruitful work to recruit the media as a social policy to highlight the factors affecting the health and health promotion [94].…”
Section: Discussion and Recommendationmentioning
confidence: 99%
“…For example, the article accompanying the brief on residential segregation described how a local resident's neighborhood left her isolated from needed resources (43). As journalists know, such narratives can be effective in communicating health information and persuading audiences (59). Steady coverage by the media partners also spurred reporting by other local news outlets such as St. Louis Public Radio and the daily St. Louis Post-Dispatch newspaper.…”
Section: A Local Example: For the Sake Of Allmentioning
confidence: 99%
“…Yet, political leaders tend to come from higher socioeconomic groups in society and may feel no personal stake in policy outcomes (Neiderdeppe et al 2008). Raising awareness of the social determinants of health among political elites may ultimately involve, as Neiderdeppe et al have argued, the difficult challenge of convincing higher socioeconomic groups to forego their own self interest and consider the plight and circumstances of low socioeconomic groups in formulating policy (Neiderdeppe et al 2008). Even under those conditions in which increased awareness has occurred among policymakers, there will be a failure to influence behavior, specifically policy change, if supporting structures are not in place to enable, reinforce, or push for change (Green and Kreuter 2005).…”
mentioning
confidence: 99%
“…Research has suggested that policymakers should be the primary targets of campaigns to raise awareness on the social determinants of health since their views, as opposed to the views of specific constituencies, tend to shape the final form of policies (Bartels et al 2005;Neiderdeppe et al 2008). Yet, political leaders tend to come from higher socioeconomic groups in society and may feel no personal stake in policy outcomes (Neiderdeppe et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation